2006
DOI: 10.1093/nar/gkl956
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy of Escherichia coli σ 70 promoters

Abstract: Information theory was used to build a promoter model that accounts for the −10, the −35 and the uncertainty of the gap between them on a common scale. Helical face assignment indicated that base −7, rather than −11, of the −10 may be flipping to initiate transcription. We found that the sequence conservation of σ70 binding sites is 6.5 ± 0.1 bits. Some promoters lack a −35 region, but have a 6.7 ± 0.2 bit extended −10, almost the same information as the bipartite promoter. These results and similarities betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
263
2
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(287 citation statements)
references
References 110 publications
(238 reference statements)
21
263
2
1
Order By: Relevance
“…1B; Koo et al 2009a,b). Consistent with this, the information content of the core regions of s 32 promoters (18.3 bits) (Shultzaberger et al 2007). Requiring extensive recognition determinants would limit transcription to a relatively restricted set of promoters, making it important to understand how these ss maintain dependence on all three promoter motifs.…”
supporting
confidence: 57%
“…1B; Koo et al 2009a,b). Consistent with this, the information content of the core regions of s 32 promoters (18.3 bits) (Shultzaberger et al 2007). Requiring extensive recognition determinants would limit transcription to a relatively restricted set of promoters, making it important to understand how these ss maintain dependence on all three promoter motifs.…”
supporting
confidence: 57%
“…The rplY promoter is negatively regulated by ppGpp and transcription factor DksA Analysis of the rplY upstream regions in sequenced genomes of E. coli and related bacteria (NCBI Gene database) revealed that the presumable rplY promoter possesses features typical of the σ 70 -dependent promoters (Harley and Reynolds 1987;Schultzaberger et al 2007), including a "good" putative −10 element (TAg/ tAAT) separated from a −35 hexamer (bearing a universally conserved TTG triplet) by an optimal spacer region of 17 bp (Fig. 1A).…”
Section: Resultsmentioning
confidence: 99%
“…The results of this work, together with results of previous work, establish that TSS selection involves at least four promoter sequence determinants: (i) position relative to the −10 element (preference for the position 7-bp downstream of the −10 element) (5-11); (ii) sequence of TSS T and TSS-1 T (strong preference for pyrimidine at TSS T and preference for purine at TSS-1 T , which enable initiation with a purine NTP and maximize stacking between DNA bases and the initiating purine NTP) (11,(17)(18)(19)(20); (iii) sequence of the discriminator element (preference for TSS selection at upstream positions for discriminator sequences that disfavor scrunching and preference for TSS selection at downstream positions for discriminator sequences that favor scrunching) (13,14); and (iv) sequence of the CRE (preference for G at TSS+1 NT ). In addition to these sequence determinants, DNA topology and NTP concentrations also influence TSS selection (6,8,9,11,(21)(22)(23)(24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%